PENGARUH GERAKAN LITERASI SEKOLAH TERHADAP KREATIVITAS SISWA (NASIONAL) - Tia Irawan; Dheni Harmaen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2020)
GLS is an effort in the form of participatory activities by involving school residents so that students get used to reading. Various studies that say that the literacy ability of students in Indonesia is quite alarming. Based on the author's observations, the library that should be used as a place to read books is only used as a place to store books. so with this GLS, it is expected that students' reading literacy skills will increase. This study aims to describe the teacher's understanding of the GLS and to describe the implementation that teachers do to support the student literacy movement nationally. The approach in this study uses a qualitative approach. Qualitative approach is used to describe, describe, explore and describe related to this research. While the type of research used in this research is descriptive qualitative. The results showed that the teacher's understanding of the national student literacy movement was quite good, and adapted to the abilities of the students, while the teacher's implementation was still focused on improving reading and writing skills and increasing self-confidence, namely through singing the national compulsory anthem, reading Alternately illustrated story books are provided in the reading corner and library, while the activities carried out in the GLS are reading short letters, singing the national anthem, and reading multiplication. The conclusion from the above findings is that in its implementation it is not only in the fields of linguistics and literature, mathematics, and science but also in the fields of religion and SBDP. It looks on the activities carried out in the implementation of literacy activities nationally although not yet maximal.